Aspirin inhibits proteasomal degradation and promotes α-synuclein aggregate clearance through K63 ubiquitination - Jing Gao; Yang Liu; Chenfang Si; Rui Guo; Shouqiao Hou; Xiaosong Liu; Houfang Long; Di Liu; Daichao Xu; Zai-Rong Zhang; Cong Liu; Bing Shan; et al. (Nature Communications)
Abstract Aspirin is a potent lysine acetylation inducer, but its impact on lysine ubiquitination and ubiquitination-directed protein degradation is unclear. Herein, we develop the reversed-pulsed-SILAC strategy to systematically profile protein degradome in response to aspirin. By integrating degradome, acetylome, and ubiquitinome analyses, we show that aspirin impairs proteasome activity to inhibit proteasomal degradation, rather than directly suppressing lysine ubiquitination. Interestingly, aspirin increases lysosomal degradation-implicated K63-linked ubiquitination. Accordingly, using the major pathological protein of Parkinson’s disease (PD), α-synuclein (α-syn), as an example of protein aggregates, we find that aspirin is able to reduce α-syn in cultured cells, neurons, and PD model mice with rescued locomotor ability. We further reveal that the α-syn aggregate clearance induced by aspirin is K63-ubiquitination dependent in both cells and PD mice. These findings suggest two complementary mechanisms by which aspirin regulates the degradation of soluble and insoluble proteins, providing insights into its diverse pharmacological effects that can aid in future drug development efforts.